PELATIHAN PENGOLAHAN AIR SUNGAI SIAP KONSUMSI DI KELURAHAN KERAMASAN KECAMATAN KERTAPATI SUMATERA SELATAN - Masayu Rosyidah; Rizka Mayasari; Yasmin (Universitas katolik Musi Charitas, 2018)
ABSTRACT Unavailability of clean water in accordance with water quality standards and the lack of knowledge of local Keramasan village communities to manage water that is safe, it is necessary to do a workshop / training design and processing of drinking water. The workshop aims to open insight, improve the knowledge and skills of the community in drinking water treatment training for the residents of Keramasan Kertapati. The service method is carried out by conducting training on the design of water filter devices, which are then channeled to ultra violet sterilizers to kill or kill pathogenic microorganisms in water so that the water can be drunk directly. The results of this service are expected to help the community to get water that is suitable for consumption independently and to provide understanding and improvement in the quality of health for the community